Dokter Pustaka Inovasi Layanan Masa Pademi Covid-19 Di Perpustakaan Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan Universitas Gadjah Mada - Sukirno Sukirno (IAIN Ponorogo, 2020)
The Covid-19 pandemic has changed everything a lot, as well as providing services. During the Covid-19 pandemic, all face-to-face services were eliminated. During a pandemic, services must continue and must not reduce the quality of service. Staff in agencies, both public and private, do various ways to keep providing good service. Creativity and innovation are highly demanded in providing services during the Covid-19 pandemic. Library of the Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada to provide services to users by innovating service facilities, namely Doctor of Library. Doctor of Library online service to the academic community and alumi for requests for scientific information. Doctor Pustaka facilities are installed on the library website address http://libmed.ugm.ac.id. Hopefully, with the Doctorof Libary, requests for scientific information on the Covid-19 pandemic will still be well served.